2014
DOI: 10.14417/ap.854
|View full text |Cite
|
Sign up to set email alerts
|

Percepção de Competência Parental: Exploração de domínio geral de competência e domínios específicos de auto-eficácia, numa amostra de pais e mães portuguesas

Abstract: A avaliação que os pais fazem sobre o seu próprio desempenho pode ter um papel directo ou indirecto no desenvolvimento das crianças. Neste trabalho, estudamos o sentimento de competência parental face ao papel global da parentalidade e as percepções de auto-eficácia em domínios específicos da parentalidade, procurando identificar diferenças entre pais e mães, e discernir efeitos possíveis face a características demográficas, como preditores das cognições da parentalidade. Os resultados vão de encontro a evidên… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
3
0
5
Order By: Relevance
“…Regarding the feeling of self-efficacy at children's sadness, the data reinforce results published in a previous study (Ferreira et al, 2014) that showed fathers and mothers feeling less self-effective when dealing with such situations, which is called "empathic responsiveness" in the literature (Ferreira et al, 2014;Guillamón et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding the feeling of self-efficacy at children's sadness, the data reinforce results published in a previous study (Ferreira et al, 2014) that showed fathers and mothers feeling less self-effective when dealing with such situations, which is called "empathic responsiveness" in the literature (Ferreira et al, 2014;Guillamón et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the relationships established between the parental peers, individual efforts to handle the specific demands of each situation are observed. Among these concepts, self-efficacy has been investigated to understand the behavior of caregivers of children with disabilities regarding the competencies related to care or parental competence (Ferreira et al, 2014).…”
mentioning
confidence: 99%
“…Para além disto, a interação do pai com o bebê com um ano de vida pode estar também relacionada ao envolvimento do pai desde a gestação, e que vai se ampliando ao longo do tempo (Tamis-LeMonda, Kahana-Kalman, & Yoshikawa, 2009). Soma-se a isto o fato de os pais muitas vezes terem uma percepção de menor eficácia parental quando comparando à mãe (Ferreira et al, 2014 Mesmo existindo em nossa sociedade a tendência a uma atualização do papel paterno, que passou a ser mais participativo (Vieira et. al, 2014), muitos pais do presente estudo ainda pareceram apoiar seu envolvimento em aspectos típicos e esperados de um pai mais tradicional -embora não menos importantes -, como ser provedor para retratar sua paternidade como positiva.…”
Section: Discussionunclassified
“…According to the literature, perceived parental competence is a factor that is related to parental satisfaction, which is essential to child well-being and can contribute to healthy family relations (Matias et al, 2017). In this sense, perceived parental competence refers to parent's perception (Pardo et al, 2018) and expectations of their own role as parents (Ferreira et al, 2014). Studies showed that greater perceived parental competence is positively associated with positive parental practices (Dekovic et al, 2010;Tristão et al, 2015), better mother-infant interaction (Chung et al, 2018) and child well-being (Nunes & Ayala Nunes, 2016).…”
Section: Introductionmentioning
confidence: 99%